2011
DOI: 10.1016/j.envsci.2010.10.011
|View full text |Cite
|
Sign up to set email alerts
|

Catchments, sub-catchments and private spaces: Scale and process in managing microbial pollution from source to sea

Abstract: Exeter. He is a rural policy specialist and a rural sociologist with particular interests in applying interdisciplinary approaches to policy-relevant research and in direct engagement in the policy process.David Oliver is senior research fellow in the Centre for Sustainable Water Management in the Lancaster Environment Centre, Lancaster University. His research background is in soil hydrology and water flow pathways, and microbial transfer and survival within agricultural

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(7 citation statements)
references
References 54 publications
(51 reference statements)
0
7
0
Order By: Relevance
“…Plot studies are essential to help consolidate understanding and scale up findings from laboratory-based investigations to field and catchment scales ( Winter et al., 2011 ). It is therefore critically important that plot scale studies of FIO persistence are undertaken to complement observations made at smaller scales and to provide evidence of impacts of complex interacting environmental factors on FIO survival ( Oliver et al., 2016a ).…”
Section: Discussionmentioning
confidence: 99%
“…Plot studies are essential to help consolidate understanding and scale up findings from laboratory-based investigations to field and catchment scales ( Winter et al., 2011 ). It is therefore critically important that plot scale studies of FIO persistence are undertaken to complement observations made at smaller scales and to provide evidence of impacts of complex interacting environmental factors on FIO survival ( Oliver et al., 2016a ).…”
Section: Discussionmentioning
confidence: 99%
“…For instance, the previously alluded to study of two beaches in northwest England found that water draining from farms and farmland accounted for 55 percent of "pollution" at one beach [Walney] and 25 percent at the other [Morecambe] (Dunphy 2013, 5). In many ways, this pollution can be seen as an issue of farm management-a full discussion of which extends beyond the purposes of this chapter (but see, for instance, Winter et al 2011). Instead, my interest is more in how animals have come to be made present in bathing waters in spite of their physical (or topographical) distance.…”
Section: Animal Flows and Tracesmentioning
confidence: 99%
“…These need to take account of multiple pollution sources, pathways and impacts (cf. Collins and Walling, 37 Haygarth et al, 38 Johnes et al, 39 Hewett et al, 40 Winter et al, 41 Collins et al 42 ) alongside the activities and motivations of a wide range of stakeholders.…”
Section: Challenges For Catchment Researchmentioning
confidence: 99%
“…Such barriers take time to break down and it is only relatively recently that the environmental science research community has started to address the issue by building research programmes that are delivered by multi-disciplinary consortia (e.g. Winter et al 41 ). Breaking down communication barriers between academic disciplines can be seen as a rst step towards tackling the multi-dimensional, complex issues faced by policy makers and other end-users of environmental research.…”
Section: Organising Collaborative Approaches To Researchmentioning
confidence: 99%